2021
DOI: 10.3389/fpsyg.2021.585816
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Improves the Sleep Quality in Disabled Elders: The Role of Perceived Stress

Abstract: The current research aims to prove the impact of resilience on sleep quality and to investigate the mediating function of perceived stress in the paths from resilience to sleep quality among disabled Chinese elders. The participants were 196 elders with visual and physical disability who resided in the nursing houses in Shanghai, including 102 males and 94 females whose mean age was 74.5 years old (standard deviation = 6.81). All the elders were measured with the 10-item Connor-Davidson Resilience Scale, Pitts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…For home-cage assessments, this system is particularly advantageous in that a full circadian rhythm could be captured in a single recording (with upward of 72 h before changing batteries), allowing the possibility for the recording of multiple days of sleep staging in one subject without intervention. This, paired with the consistent PhenoTyper-mediated sleep disruption paradigm we describe, can help elucidate sleep resilience in response to stress and deprivation, as well as how this is altered with disease and age ( Brieva et al, 2021 ; Cai et al, 2021 ; Casale et al, 2021 ).…”
Section: Discussionmentioning
confidence: 88%
“…For home-cage assessments, this system is particularly advantageous in that a full circadian rhythm could be captured in a single recording (with upward of 72 h before changing batteries), allowing the possibility for the recording of multiple days of sleep staging in one subject without intervention. This, paired with the consistent PhenoTyper-mediated sleep disruption paradigm we describe, can help elucidate sleep resilience in response to stress and deprivation, as well as how this is altered with disease and age ( Brieva et al, 2021 ; Cai et al, 2021 ; Casale et al, 2021 ).…”
Section: Discussionmentioning
confidence: 88%
“…Consequently, their QoL could also be maintained better. Similarly, Yumei Cai et al pointed out that resilience was negatively correlated with sleep disturbance, which was associated with positive individual health status ( 24 ). However, few studies examined sleep disturbance as a mediator between resilience and QOL among glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study on the QoL of pregnant women also stated that stress caused physical and mental responses that affected people’s resilience. In turn, these physiological and psychological outcomes were found to be associated with sleep disturbance ( 23 , 24 ). Therefore, we hypothesize that sleep disturbance will play a mediating role between resilience and the QoL of glaucoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally, resilience appeared to be a protective factor for sleep quality. When suffering from stress and trauma, a strong level of resilience helps to improve the quality of sleep [30]. A large longitudinal study of pregnant women in Finland showed that higher levels of resilience predicted better sleep quality [47].…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is de ned as "having not only important psychological skills or abilities, but also the ability of the individuals to use family, social and external support systems to better cope with stress" [29]. Previous research has found that an individual's resilience is associated with their sleep quality, and low resilience leads to poorer sleep quality [30]. But Some individuals who are stressed and worried don't tend to suffer from poor sleep quality, and part of the reason was the high resilience.…”
Section: Introductionmentioning
confidence: 99%